GANGGUAN BELAJAR PADA ANAK BERKEBUTUHAN KHUSUS DI MI MA’ARIF MAGUWOHARJO SLEMAN YOGYAKARTA - Fadlillah, Muhammad (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
Child with learning disorder is one kind of children with special needs. The symptoms of this learning disorder are difficultto concentrate and understand new information resulting from nervous and brain function disorders. Children who experiencelearning disorder will show different attitudes from others, such as like yelling, daydreaming, being frightened, and running toand fro. These attitudes are expressed by Rumiyati Diah Sekar Purwaningsih, a student diagnosed with learning disorder.This learning disorder can be treated with therapy on a regular basis, such as speech therapy, habituation, and social therapy.In addition, early prevention can also be done at prenatal and postnatal time.